FRI0651 Quantitative chest ct predicts 8-years-mortality and comorbidity in systemic sclerosis. (12th June 2018) - Ariani, A.; Silva, M.; Bravi, E.; Saracco, M.; Parisi, S.; De Gennaro, F.; Idolazzi, L.; De Santis, M.; Girelli, F.; Lumetti, F.; Volpe, A.; Santilli, D.; et al.
Abstract : Background: Interstitial Lung Disease (ILD) is the main cause of death in Systemic Sclerosis (SSc). Serious lung involvement increase the hospitalization rate and sometimes oxygen therapy is required. An prompt treatment in ILD-SSc patients is essential, but nowadays there is not a feasible method to identify patients with poor prognosis. Although chest Computed Tomography (CT) is the gold standard to detect ILD, there is no standardized assessment of its severity. Quantitative CT (QCT) is an innovative and operator independent method to assess ILD-SSc extent and severity. An increasing number of evidences confirm that QCT is extremely useful for detecting SSc-ILD with the worst prognosis. However is not well established if QCT can predict death or comorbidity associated to ILD. Objectives: The main aim of this study is to verify if QCT predict 8-years mortality or clinical worsening (i.e. hospitalization for respiratory complications or chronic oxygen therapy) in SSc. Methods: Consecutive SSc patients (according to ACR/EULAR classification criteria) from ten different centers underwent a chest CT. Their clinical history was carefully recorded in the following 96 months. A rheumatologist post-analyzed every CT with an open source DICOM viewer in order to obtain QCT indexes. Patients were clustered in two subgroups: according to QCT indexes' cutoff previously found (see Ariani et al., 2017). The survival time of each patient was considered the time interval between the CT date and death, hospitalization related to lung worsening, beginning of chronic oxygen therapy or last medical examination Results: We enrolled 342 patients; during the 8-years follow-up 15.5% (53/342) died and 4, 4% (15/342) had a clinical worsening. The Kaplan-Meier survival analysis demonstrates a worse survival in patients with QCT indexes above or below the previously observed cutoffs. (p<0.01). In particular the QCT index cutoff which the best performance was total lung kurtosis (tKurt) equal to 4.89 (p<0.0001). References: The QCT indexes' cutoffs previously found (see Ariani, et al., 2017) identify the SSc-ILD subjects with an high risk of 8-years mortality and comorbidity. These findings suggest that QCT could became a pivotal assessment in SSc management because its role in identifying patients with poor prognosis and who deserve an early aggressive treatment. Disclosure of Interest: None declared